2015
DOI: 10.4102/sajems.v18i2.761
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based discrimination in South Africa: A quantitative analysis of fairness of remuneration

Abstract: Equity is important to most individuals and its perceived absence  may impact negatively on individual and organisational performance. The concept of equity presupposes fair treatment, while discrimination implies unfair treatment. The perceptions of discrimination, or being treated unfairly, may result from psycho-social processes, or from data that justifies discrimination and is quantifiable. Objectives: To assess whether differences in post grading and remuneration for males and females are based on gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Job analysis data can distinguish the knowledge, skills, abilities, and expertise which are necessary for effective and high level of performance. It can build criteria for selection, hiring, promotions, plan and create objectives for employee training and organization development programs, establish performance measurement standards and develop it, and assist in determining compensation classification levels (Steyn and Jackson, 2015). Atteya (2012) pointed out that the selection and recruitment process is one of the most important factors that affect the performance of employees and productivity.…”
Section: Job Analysismentioning
confidence: 99%
“…Job analysis data can distinguish the knowledge, skills, abilities, and expertise which are necessary for effective and high level of performance. It can build criteria for selection, hiring, promotions, plan and create objectives for employee training and organization development programs, establish performance measurement standards and develop it, and assist in determining compensation classification levels (Steyn and Jackson, 2015). Atteya (2012) pointed out that the selection and recruitment process is one of the most important factors that affect the performance of employees and productivity.…”
Section: Job Analysismentioning
confidence: 99%
“…The ILO has noted that, without targeted action, at the current rate, pay equity between women and men will not be achieved before 2086 (ILO 2016). Steyn and Jackson (2015) also reported evidence of gender-based wage differences in a selection of South African companies. They found evidence for higher post gradings and salary for males compared with those of females.…”
mentioning
confidence: 97%
“…In another study conducted Steyn and Jackson (2015) among 1740 employees in South Africa to assess whether job grading and salaries for male and female employees were varied on the basis of gender, as opposed to quantifiable variables, it was found that male employees held higher positions and salaries compared to their female counterparts although the difference was statistically insignificant. Despite efforts put into place by organizations to stamp out sexual harassment in the workplace, a study conducted by Mendez, Snyder, Scherer and Fisher (2012) in the US found that the vice is still rampant in organizations.…”
Section: Gender Sensitivity and Performancementioning
confidence: 99%